Proposal of a postal quality control system for the treatment planning system in teletherapy using OSL nanodot dosimeter - Rodríguez Horna, Ángel (2022)
Objective: To implement a Postal Quality Control System to verify the Treatment Planning System in Teletherapy using Dosimeters Al2O3 :C, based on optically stimulated luminescence (OSL), commercially known as OSLD nanoDotTM.  Materials and Methods: A mannequin containing OSLD nanoDot TM dosimeters, (Al2O3 :C), previously characterized and calibrated for the energy of a 6.0 MV x-ray beam generated in a linear accelerator, the absorbed dose values were measured with: a Semiflex, ionization chamber, PTW – Freigburg electrometer,  3D radiation geometries, such as: Simple geometry (open field at 0º and 25º), Complex geometry (three open fields at 0º, 90º and 270º) and Combined geometry (field and various variations of Gantry rotation), using square fields (6cm2), circular (diameter 6cm), oblique (6cm x 6cm) and Irregular, equal weights and virtual wedge filters in different regions of the photon beam.  Results: The values of the characterization of the nanodot OSLD were: homogeneity (0.9999), by fading over time (0.9989), by correction of depletion (0.9985), of reproducibility (0.9953), by angular dependence (0.9925) and by linearity (1.0000) for a range of absorbed doses 100cGy to 200cGy.  The evaluations in the different regions of the beam, in homogeneous medium, were the following: Simple geometry (Uncertainty: 3.01%), Complex geometry (Uncertainty: 2.16%) and Combined geometry (Uncertainty: 2.62%) Conclusions: The results obtained are within the tolerance values, thus concluding that the OSLD nanoDot TM is a highly reliable dosimeter, in addition to its convenience in its integration into a postal dosimetric audit program.